"UZBEKISTAN TEMIR YOLLARI" JSC MACHINISTS PROPOSAL FOR DIGITALIZATION OF QUALIFICATION CERTIFICATE (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Year 2020 of the President of the Republic of Uzbekistan After the signing of Decree No. PF-6079 dated October 5, the implementation of complex measures for the active development of the digital economy in our country, the wide introduction of modern information and communication technologies in all industries and sectors, first of all, in public administration, education, health care and agriculture began to be emphasized. In these measures, attention can also be paid to proposals or methods of introducing or creating new types of technologies, and taking into account the above, it is required to create new types of technological processes in the development of each company. The main freight transportation of the railway system is carried out by locomotives, which are driven by drivers. By itself, each driver can gain experience from year to year or change the type of control locomotive and change the type of train control based on his skills. In this case, they will be presented with a qualification level, and I would like to make a proposal to digitize the qualification level certificates by transferring them to a discount card.